Evolution of a mimicry supergene from a multilocus architecture - Jones, Robert T. (The Royal Society, 2012)
The origin and evolution of supergenes have long fascinated evolutionary biologists. In the polymorphic butterfly Heliconius numata, a supergene controls the switch between multiple different forms, and results in near-perfect mimicry of model species. Here, we use a morphometric analysis to quantify the variation in wing pattern observed in two broods of H. numata with different alleles at the supergene locus, ‘P’. Further, we genotype the broods to associate the variation we capture with genetic differences. This allows us to begin mapping the quantitative trait loci that have minor effects on wing pattern. In addition to finding loci on novel chromosomes, our data, to our knowledge, suggest for the first time that ancestral colour-pattern loci, known to have major effects in closely related species, may contribute to the wing patterns displayed by H. numata, despite the large transfer of effects to the supergene.